Halal Supply Chain Performance Measurement with Supply Chain Operations Reference Approach - Herlina, Rohma; Iskandar, Yelita Anggiane; Sukarno, Iwan (Institut Transportasi dan Logistik Trisakti, 2024)
Bakso Mantul is a household industry produces ready-to-eat packaged frozen meatballs with sales areas in South Sumatra, Indonesia. The absence of halal certification of the products failed the business to get benefit of increasing income and consumer’s trust. The obligation to certify halal products is based on the Law of the Republic of Indonesia No. 33 of 2014. The preparation and performance measurement of halal supply chain management implemented by Micro, Small, and Medium Enterprises (MSMEs) could support to obtain the certification. The purpose of the study is to prepare Key Performance Indicators (KPIs) using Supply Chain Operations Reference (SCOR) as a form of standardization. SCOR could be used to maintain the products’ halal quality and measure the performance of all halal supply chain activities in the cycle view push process. From the validation results carried out by internal and external respondents of MSMEs, 12 KPIs obtained are considered valid and could be used to measure the performance of halal supply chain. From the measurement, a value of 50.78 is still categorized as average based on the Snorm De Boer system. The KPI analysis using the Traffic Light System (TLS) shows that seven KPIs are satisfying, four are not satisfactory, and one is marginal.